2016
DOI: 10.3897/zookeys.632.9747
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the continental fishes of the state of Chiapas, Mexico, and their distribution

Abstract: An updated checklist of the distribution of fishes that inhabit the continental waters of the Mexican state of Chiapas is presented. The state was compartmentalized into 12 hydrological regions for the purpose of understanding the distribution of fish fauna across a state with large physiographic variance. The ichthyofauna of Chiapas is represented by 311 species distributed in two classes, 26 orders, 73 families, and 182 genera, including 12 exotic species. The families with the highest number of species were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…), L. enigmatica is uncommon in the local fisheries, as we only observed 2 specimens in March, which corresponds to the dry season in the region (Instituto Nacional de vulcanología, meteorología e hidrología 2018). Other studies also reported low abundandes of L. enigmatica in the Río Lacantun (Lozano-Vilano et al 2007), which supports making this species a high priority for conservation (Velázquez-Veláquez et al 2016).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…), L. enigmatica is uncommon in the local fisheries, as we only observed 2 specimens in March, which corresponds to the dry season in the region (Instituto Nacional de vulcanología, meteorología e hidrología 2018). Other studies also reported low abundandes of L. enigmatica in the Río Lacantun (Lozano-Vilano et al 2007), which supports making this species a high priority for conservation (Velázquez-Veláquez et al 2016).…”
Section: Discussionmentioning
confidence: 75%
“…The uncertainty about the occurrence of L. enigmatica in the Usumacinta river basin can be explained by the cryptic nature of this species and the lack of ichthyological studies in the upper basin (Velázquez-Velázquez et al 2016, Soria-Barreto et al 2018. Moreover, most of the previous studies are biased by location access and/or sampling gear, as usually happens with biodiversity surveys (Boakes et al 2010, Wehi et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lagoon-estuarine systems of the Mexican south Pacific have been poorly studied in terms of ichthyofaunal richness, new records of fish have recently been reported (Velázquez-Velázquez et al 2016, Hernández-Roque et al 2018, Romero-Berny et al 2018. The intensification of samplings and the analysis of bycatch and landings from artisanal fisheries in specific intertidal environments (e.g., lagoon mouths, channels, mangroves, and swamps) could increase the known richness of the fish fauna.…”
Section: Discussionmentioning
confidence: 99%
“…Es probable que la elevada riqueza del sistema se encuentre relacionada con la amplitud de la boca y morfología de la laguna, factores que favorecen una conectividad permanente con el ambiente oceánico (Mendoza et al 2009). Es interesante mencionar que cuatro de los nuevos registros (27%) corresponden a la familia Ophichthidae, la cual se encontraba poco representada en los ambientes costeros continentales de Chiapas (Velázquez-Velázquez et al 2016). También, es importante destacar el papel de los estudios sobre fauna acompañante de la pesca en la ampliación del conocimiento de la diversidad íctica (López-Martínez et al 2010).…”
Section: Discussionunclassified